Integrating Social Emotional Intelligence into Project-Based Learning: Enhancing Web Programming Competencies in Vocational Education - Mukarromah, Hana Zainab; Mashoedah (International journal of technology and education research, 2026)
The rapid evolution of the digital industry demands that vocational education graduates possess not only technical proficiency but also robust social-emotional competencies. However, a critical disparity exists in current vocational pedagogy, where technical instruction often overlooks the collaborative and emotional skills vital for the modern workforce. This study investigates the efficacy of integrating Social Emotional Intelligence (SEI) into Project-Based Learning (PjBL) to enhance web programming competencies at SMK Negeri 4 Bandung. Employing a quasi-experimental design with 70 students, data were collected via cognitive pretest-posttest assessments, SEI scales, and motivation questionnaires. The results revealed a statistically significant difference in learning outcomes (Sig. 0.010 < 0.05), with the experimental group achieving a moderate N-Gain of 0.62, substantially outperforming the control group's low N-Gain of 0.30. Furthermore, path analysis confirmed that SEI significantly influences learning motivation, which functions as a partial mediator for academic achievement. These findings contribute a novel pedagogical framework for vocational education, demonstrating that integrating emotional intelligence into technical training is essential for fostering holistic student development and professional readiness.